Not All Related Party Transactions (RPTs) Are the Same: Ex Ante Versus Ex Post RPTs - RYNGAERT, MICHAEL; THOMAS, SHAWN (Journal of Accounting Research, 2012)
ABSTRACT Related party transactions (RPTs) are potential means for insiders to expropriate outside shareholders via self‐dealing. There are, however, possible benefits to these arrangements for outside shareholders. We find that the overall volume of disclosed RPTs is generally not significantly associated with shareholder wealth as measured by operating profitability or Tobin's Q. However, the results for total RPT volume obscure that ex ante RPTs, transactions that predate a counterparty becoming a related party, are innocuous at worst in terms of their association with operating profitability and significantly positively associated with Tobin's Q whereas ex post RPTs, transactions initiated after a counterparty becomes a related party, are significantly negatively associated with operating profitability. Ex post RPTs also result in significant share price declines when first disclosed and are associated with an increased likelihood that a firm will enter financial distress or deregister its securities. These results are consistent with ex post RPTs serving as means for insiders to expropriate outside shareholders.